Critical Study of the Application of Muhkam and Mutasyabih Verses in Tafsir Studies - Zahrah Faizatun Nafi'ah; lham Nabil Aufa; Achmad Sumitro Iqbal Shalahuddin Al-Ayubi (An-Nur International Journal of The Quran & Hadith, 2025)
This study discusses theological and epistemological debates on muhkam and mutasyabih verses in Qur’anic studies, which, since the classical period, have centered on the tension between tafwidh and ta’wil. These debates arise from different approaches to understanding verses whose meanings are considered clear or ambiguous. The research is motivated by the need to reexamine this issue within the context of contemporary Indonesian Qur’anic interpretation, focusing on two influential mufassirs: Hamka in Tafsir Al-Azhar and Quraish Shihab in Tafsir Al-Mishbah. These works represent moral-spiritual and rational-linguistic interpretive tendencies, respectively. The study employs a qualitative library research method, drawing on primary sources such as tafsir literature and ʿulum al-Qur’an texts, as well as secondary sources including academic books and scientific articles. Data are analyzed using content analysis to identify key interpretive patterns related to muhkam and mutasyabih verses. The findings indicate that the muhkam–mutasyabih debate is rooted in human limitations in comprehending the language and structure of revelation. Discussions on muqatta‘ah letters emphasize the transcendence of divine revelation, while theological analysis shows that mutasyabihat verses contribute to the development of reasoning and spirituality in Islam. Both Hamka and Quraish Shihab offer moderate syntheses that balance reason and faith, affirm tawhid, and maintain the relevance of Qur’anic interpretation in modern Islamic thought.